2017
DOI: 10.1159/000463395
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Estimates of Glomerular Filtration Rate Based on Creatinine and Cystatin C: Importance of Body Composition

Abstract: Background: Creatinine and cystatin C concentrations are commonly used to estimate glomerular filtration rate (eGFR) in clinical practice and epidemiological studies. To estimate the influence of different body composition measures on eGFR from creatinine and cystatin C blood concentrations, we compared the associations of different anthropometric and body composition measures with eGFR derived from creatinine (eGFRcreat) and cystatin C (eGFRcystC) blood concentrations. Methods: In a popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…This present study also found a negative correlation between the anthropometric parameters and serum Cystatin C. This suggested that Cystatin C may not be independents of anthropometric indices as earlier documented by some researchers [21,22]. In keeping with this finding is a recent study that involved a large cohort of children (4,305 children) in the Netherlands that demonstrated the influence of body composition on both the value of serum Cystatin C and estimated GFR [32].…”
Section: Discussionsupporting
confidence: 89%
“…This present study also found a negative correlation between the anthropometric parameters and serum Cystatin C. This suggested that Cystatin C may not be independents of anthropometric indices as earlier documented by some researchers [21,22]. In keeping with this finding is a recent study that involved a large cohort of children (4,305 children) in the Netherlands that demonstrated the influence of body composition on both the value of serum Cystatin C and estimated GFR [32].…”
Section: Discussionsupporting
confidence: 89%
“…The low correlation coefficient of r 2  = 0.003 ( p  < 0.001) may explain why no correlation with lean or fat mass percentage was found by Miliku et al in 6-year-old children [23, 44]. The estimation of the GFR based on sCrea must also consider the body height (Schwartz et al) [4] during entire childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…CysC appears to be more sensitive than Cr for patients with declining GFR in chronic liver disease (3)(4)(5). However, CysC positively correlates with body mass index (BMI) and is more strongly correlated with waist circumference and inflammation (6)(7)(8). In patients with chronic kidney disease (CKD) with eGFR >60 ml/min/m 2 , the medium value of Cr was well within the normal range, whereas the median value of CysC was found to be higher than the upper reference limit (7).…”
Section: Introductionmentioning
confidence: 99%